Complexity in internal medicine wards: A novel screening method and implications for management. Issue 1 (10th January 2018) - Bandini, Fabrizio; Guidi, Stefano; Blaszczyk, Silvia; Fumarulo, Antonietta; Pierini, Michela; Pratesi, Paolo; Spolveri, Stefano; Padeletti, Margherita; Petrone, Pasquale; Zoppi, Paolo; Landini, Giancarlo
Abstract: Rationale: Complexity is increasingly recognized as a critical variable in health care. However, there is still lack of practical tools to assess it and tackle the challenges that stem from it, particularly within hospitals. Aims and objective: To validate a simple novel screening method based on both objective and subjective criteria to identify patients with clinically complex hospitalization events. To evaluate the prevalence of patients with complex events, identify their features, and compare them with those of the other patients and to those of patients with multimorbidities. Method: We monitored the level of complexity of the hospitalization events of 240 patients admitted to an internal medicine ward in Tuscany over the course of 56 days. We compared the demographic features, the length of stay, and the prognosis of patients with and without complex events. Results: Sixty‐nine patients (28.8% of the sample) had a complex episode during their stay, and 115 (47.9%) had phases of low complexity. Patients with complex episodes were younger and more comorbid than patients without. They stayed longer in‐hospital (+4.5 days; 95% CI: 2.5‐6.5) and had higher mortality (OR: 24.93; 95% CI: 6.97‐171.63) and a lower probability of home discharge (OR: 0.25; 95% CI: 0.13‐0.48). Conclusions: The results show that using a simple screening method is possible to identify complex patients within IM wards and that every day, about one‐third of the patients are complex. The results are discussed in implications for the dynamic management of patients with complex and simple phases during hospitalization.